Electrode assembly
By uniformly applying pressure and heat to the entire laminate during the manufacturing of electrode assemblies, the issues of non-uniform adhesion and reduced performance in conventional processes are addressed, resulting in enhanced stability and energy density.
Patent Information
- Application Number
- JP2024232757
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2021-07-09
- Filing Date
- 2024-12-27
- Publication Date
- 2025-04-15
- Estimated Expiration
- 2042-07-08
AI Technical Summary
Conventional electrode assembly manufacturing processes face issues with non-uniform adhesion between electrodes and separation membranes due to uneven heat and pressure application, leading to reduced porosity and performance.
The electrode assembly is manufactured by applying pressure and heat uniformly to the entire laminate, rather than at each stage, to enhance stability and uniformity, and to minimize electrode shifting during the process.
This approach results in increased electrode density, improved energy density, and uniform adhesive strength across the electrode assembly, preventing loose folding and enhancing battery stability.
Smart Images

Figure 2025063108000001_ABST
Abstract
Description
[Technical field]
[0001] This application claims the benefit of the filing date of Korean Patent Application No. 10-2021-0090592 filed with the Korean Intellectual Property Office on July 9, 2021, Korean Patent Application No. 10-2021-0090588 filed with the Korean Intellectual Property Office on July 9, 2021, and Korean Patent Application No. 10-2021-0090589 filed with the Korean Intellectual Property Office on July 9, 2021, the entire contents of which are incorporated herein by reference.
[0002] The present invention relates to an electrode assembly, and more particularly, to an electrode assembly for a secondary battery. [Background technology]
[0003] Unlike primary batteries, secondary batteries are rechargeable and have the potential to be small and have large capacity, so they have been the subject of much research and development in recent years. As technological development and demand for mobile devices increases, the demand for secondary batteries as an energy source is growing rapidly.
[0004] Secondary batteries are classified into coin type batteries, cylindrical type batteries, square type batteries, and pouch type batteries according to the shape of the battery case. The electrode assembly attached inside the battery case of a secondary battery is a power generating element capable of charging and discharging, which is made of a laminated structure of electrodes and a separator.
[0005] Electrode assemblies are divided into jelly-roll type, stack type, and stack-and-folding type. In the jelly-roll type, a separator is interposed between a sheet-shaped anode and a sheet-shaped cathode coated with active material, and the entire arrangement is rolled up. In the stack type, multiple anodes and cathodes are stacked in sequence with a separator between them. In the stack-and-folding type, stacked unit cells can be rolled up on a long length of separator film.
[0006] In a conventional process for manufacturing a stack-and-fold type electrode assembly, the electrodes and separators stacked in the electrode assembly are bonded together to grip the completed stack so that it can be transported as a unit (e.g., for transporting into a battery case) without collapsing. This bonding can be achieved by applying heat and pressure to the assembled stack. However, in the conventional process for manufacturing an electrode assembly, there is a problem that the electrodes in the stack can be distorted or twisted during the heating and pressurizing process.
[0007] To solve these problems of the prior art, after each new level is added to the stack, heat and pressure are applied to the stack, and the electrodes and separators are bonded to each other during the stacking process. However, this results in a problem in that the adhesion between the electrodes and separators is largely dissipated along the stacking direction each time new heat and pressure is applied due to the accumulation of heat and pressure by the lowest component of the stack, while the upper components of the stack are relatively much weaker. Non-uniformity along the stacking direction can adversely affect the electrode assembly. For example, the lowest separator (the separator that has accumulated the most heat and pressure) can have reduced porosity and reduced performance, while the upper separators can be bonded relatively weakly to the adjacent electrodes. Summary of the Invention [Problem to be solved by the invention]
[0008] The present invention provides an electrode assembly manufactured by applying pressure and heat to the entire laminate after the components of the laminate are assembled together, rather than applying heat and pressure to the laminate at each process step. As a result, the completed electrode assembly can have better stability and improved uniformity. The present invention provides an electrode assembly with increased electrode density and increased energy density by minimizing the degree to which the electrodes stacked inside the electrode assembly are misaligned left and right based on the stacking direction of the electrode assembly. [Means for solving the problem]
[0009] One embodiment of the present invention provides an electrode assembly, comprising a plurality of electrodes arranged in a stack along a stack axis, each electrode in the stack being separated from one of the electrodes in the stack by a respective separator located therebetween along the stack axis, at least one exterior surface of the stack comprising a pattern made up of first and second regions, a second portion of the stack corresponding to the second region having a different characteristic or height than a first portion of the stack corresponding to the first region.
[0010] In one embodiment of the present invention, an electrode assembly is provided in which a second portion of the laminate corresponding to the second region has different properties from a first portion of the laminate corresponding to the first region, the properties including any of the shade and hue of at least one outer surface of the laminate, the air permeability of the separation membrane portions in the first and second regions, and the adhesive strength between the electrode and the separation membrane portions in the first and second regions.
[0011] In one embodiment of the invention, the separator is provided as an elongated separator sheet folded between each of the separators so as to extend between successive electrodes along the stacking axis along a serpentine path that traverses back and forth along a transverse direction perpendicular to the stacking axis, and each electrode in the stack includes a first side end and a second side end on opposing sides of each electrode in the transverse direction. Effect of the Invention
[0012] According to an embodiment of the electrode assembly of the present invention, a laminate in which electrodes and a separator are stacked is fixed, and then the laminate is heated and pressurized, thereby preventing the electrodes from being displaced by the press unit.
[0013] After the member fixing the laminate is removed, the laminate is heated and pressurized, and the parts that are not heated or pressurized by the member fixing the laminate are not heated or pressurized. This provides adhesion to parts where adhesion is not sufficient, thereby ensuring uniform adhesion in the electrode assembly. [Brief description of the drawings]
[0014] [Figure 1] 1 is a cross-sectional view showing an electrode assembly according to an embodiment of the present invention. [Diagram 2] FIG. 2 is a cross-sectional view of the electrode assembly of FIG. 1, illustrating the location of the upper, lower and middle portions of the electrode assembly. [Diagram 3] FIG. 2 is a perspective view conceptually illustrating a stack-up diagram of components of an electrode assembly according to one embodiment of the present invention. [Figure 4] FIG. 2 is a top view showing an electrode assembly including a first region and a second region according to one embodiment of the present invention. [Diagram 5] FIG. 2 is a perspective view showing an electrode assembly including a first region and a second region according to another embodiment of the present invention. [Figure 6] FIG. 6(a) is a perspective view showing a first press section according to one embodiment of the present invention, and FIG. 6(b) is a perspective view showing a second press section according to one embodiment of the present invention. [Explanation of symbols]
[0015] S ···Laminate O...Opening P···Folding section 10...electrode assembly 1...1st electrode 2...Second electrode 4...1st separation membrane 4a...Laminated part 4b Folding section 5...Second separation membrane 6...Side edge 50 ···First Press Department 50a, 50b: First pressure block 51 Gripper 51a Main unit 51b...Fixed part 60 ···Second Press Department 60a, 60b Second pressurizing block DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0016] The detailed description of the present invention is intended to fully explain the present invention to those having ordinary skill in the art. Throughout this specification, when a part is described as "including" a certain component, or when a certain structure and shape are described as "characterized", this means that other components, structures, and shapes may be included, without excluding other components or excluding other structures and shapes, unless otherwise specified to the contrary.
[0017] Since the present invention can be modified in various ways and can have various embodiments, a specific embodiment will be presented and described in detail in the detailed description. However, this is not intended to limit the content of the invention by the embodiment, and it should be understood that the present invention includes all modifications, equivalents, or alternatives included in the spirit and technical scope of the present invention.
[0018] Hereinafter, the present invention will be described in detail with reference to the drawings. However, the drawings are for illustrating the present invention, and the scope of the present invention is not limited by the drawings.
[0019] FIG. 1 is a cross-sectional view showing an electrode assembly 10 according to an embodiment of the present invention, and FIG. 3 is a perspective view showing electrodes 1, 2 and a separator 4 laminated on a laminate S of an electrode assembly 10 according to an embodiment of the present invention.
[0020] The electrode assembly 10 according to the present invention is a chargeable and dischargeable power generating device, and may include a stack S in which electrodes are disposed between portions of an extended separator 4 that is folded in a zigzag shape between each of the electrodes along a stacking direction Y. In this case, the electrodes may include one or more first electrodes 1 and one or more second electrodes 2 alternately arranged along the stacking direction Y.
[0021] The serpentine form of the separator 4 along the stacking direction Y may be defined by successive folds P of the separator 4, each fold P of the separator 4 wrapping around a lateral edge 6 of an electrode in a lateral direction (Z, perpendicular to the stacking direction Y) before the separator 4 extends to an opposing side of the stack S and passes between the electrode and the adjacent next electrode in the stack S. The portion of the separator 4 extending between each electrode of the stack S may be referred to as a stack of the separator 4. Thus, each layer of the stack S (defined by the position of each electrode along the stack S) may be characterized by a fold P of the separator 4 that surrounds a lateral edge 6 of the electrode on one side of the electrode from the lateral direction Z. The opposite side of the electrode along the lateral direction Z may be defined by an opening O that is characterized by a member of the separator 4 (including the fold P). Thus, the folds P may be alternately located on opposing sides of the stack S for each successive layer of the stack.
[0022] As discussed further herein, the "top surface" of the electrode assembly 10, designated by reference numeral 12 in FIG. 2, may refer to the topmost position of the electrode assembly 10 in the stacking direction of the electrode assemblies. Additionally, as mentioned herein, the "bottom surface" of the electrode assembly 10, designated by reference numeral 13 in FIG. 2, may refer to the bottommost position of the electrode assembly 10 in the stacking direction of the electrode assemblies. Finally, as discussed herein, the "middle" of the electrode assembly 10, designated by reference numeral 11 in FIG. 2, may refer to the middle position between the top and bottom surfaces of the electrode assembly 10 in the stacking direction of the electrode assembly 10. For example, if the electrode assembly 10 is made up of nine electrodes and viewed from the side, the "middle" position, as in FIG. 2, refers to the position of the fifth electrode in the stack S. Thus, subsequent references to "middle air permeability" refer to the air permeability of the separator 4 that contacts the middle electrode in the electrode assembly. Similarly, subsequent references to “intermediate adhesion” refer to the adhesion between an intermediate electrode of an electrode assembly and an adjacent portion of separator 4 .
[0023] As discussed above, the electrode assembly 10 may be provided in a form in which the outer periphery is surrounded by the external separator 5, which may be a portion (e.g., an end portion) of the same extending separator 4 along a zigzag or winding path along the separator S. In one example, the outer periphery of the electrode assembly 10 surrounded by the external separator 5 includes not only an upper surface and a lower surface in the stacking direction Y, but also at least a pair of side surfaces facing each other in the lateral direction Z. Here, the upper surface of the laminate S may refer to the outer surface forming the upper side of the laminate S in the stacking direction Y, and the lower surface may refer to the outer surface forming the lower side opposite to the upper side of the laminate S.
[0024] In one embodiment, the positive electrode may be prepared, for example, by coating a positive electrode current collector with a positive electrode coating mixture that includes a positive electrode active material, a conductive material, and a binder, and then drying the coating mixture. If necessary, a filler may be added to the mixture. Such materials may be any suitable material used in the relevant field, particularly a material commonly used for a particular application field.
[0025] Specifically, the positive electrode active material is, for example, a layered compound such as lithium cobalt oxide (LiCoO2), lithium nickel oxide (LiNiO2), or a compound substituted with one or more transition metals; 1+x Mn 2-x Lithium manganese oxides such as LiMnO4 (where x is 0 to 0.33), LiMnO3, LiMn2O3, and LiMnO2; lithium copper oxide (Li2CuO2); vanadium oxides such as LiV3O8, LiFe3O4, V2O5, and Cu2V2O7; and the chemical formula LiNi 1-x M x Lithium nickel oxide with Ni site represented by the chemical formula LiMnO2 (where M=Co, Mn, Al, Cu, Fe, Mg, B or Ga, and x=0.01 to 0.3); 2-x M x Examples of such compounds include, but are not limited to, lithium manganese composite oxides represented by Li2Mn3MO8 (where M is Co, Ni, Fe, Cr, Zn, or Ta, and x is 0.01 to 0.1) or Li2Mn3MO8 (where M is Fe, Co, Ni, Cu, or Zn); LiMn2O4 in which part of the Li in the chemical formula is replaced with an alkaline earth metal ion; disulfide compounds; and Fe2(MoO4)3.
[0026] Materials that can be used for the anode current collector are not particularly limited. The anode current collector preferably has a relatively high electrical conductivity without causing chemical changes when used in a battery. For example, stainless steel, aluminum, nickel, titanium, calcined carbon, or aluminum or stainless steel surface-treated with carbon, nickel, titanium, silver, etc. may be used. The anode current collector may be preferably aluminum. Preferably, the surface of the collector in contact with the coating mixture may include fine irregularities to increase the adhesive strength between the collector and the anode coating mixture. In addition, various forms such as a film, sheet, foil, net, porous body, foam, nonwoven fabric body, etc. are possible. The anode current collector may generally have a thickness of 3 μm to 500 μm. The conductive material contained in the anode coating mixture may generally be contained in an amount of 1 to 50% by weight of the total weight of the mixture including the anode active material. For example, graphite such as natural graphite or artificial graphite; carbon black such as carbon black, acetylene black, ketjen black, channel black, furnace black, lamp black, summer black; conductive fiber such as carbon fiber or metal fiber; metal powder such as carbon fluoride, aluminum, nickel powder; conductive whiskey such as zinc oxide or potassium titanate; conductive metal oxide such as titanium oxide; conductive material such as polyphenylene derivatives may be used.
[0027] The binder of the anode coating mixture is a component that aids in bonding between the active material and the conductive material and in binding the coating mixture to the current collector. Such binders may generally be included in an amount of 1-50% by weight of the total weight of the mixture including the anode active material. Examples of such binders include polyvinylidene fluoride, polyvinyl alcohol, carboxymethyl cellulose (CMC), starch, hydroxypropyl cellulose, regenerated cellulose, polyvinylpyrrolidone, tetrafluoroethylene, polyethylene, polypropylene, ethylene-propylene-diene terpolymer (EPDM), sulfonated EPDM, styrene butylene rubber, fluororubber, various copolymers, and the like. The filler, which is optionally added to the anode coating mixture, may be used as a component to suppress the expansion of the anode. Such a filler is not particularly limited, and may include a fibrous material that does not cause a chemical change when used in a battery. For example, olefin polymers such as polyethylene and polypropylene; glass fiber, carbon fiber, and other fibrous materials may be used.
[0028] In one embodiment, the negative electrode may be prepared by applying a negative electrode active material onto a negative electrode current collector, drying, and pressing the negative electrode active material. If necessary, the negative electrode active material may further include a conductive material, a binder, a filler, and the like as described above. In this case, a material commonly used in the art may be used. Specifically, the negative electrode active material may be, for example, carbon such as non-graphitizable carbon or graphite-based carbon; Lix Fe2O3 (0 ≦ x ≦ 1), Li x WO2 (0 ≦ x ≦ 1), Sn x Me 1-x Me' y O z (Me: Mn, Fe, Pb, Ge; Me': Al, B, P, Si, Group 1, Group 2, Group 3 elements of the periodic table, halogen; 0 < x ≦ 1; 1 ≦ y ≦ 3; 1 ≦ z ≦ 8) and other metal composite oxides; lithium metal; lithium alloy; silicon-based alloy; tin-based alloy; metal oxides such as SnO, SnO2, PbO, PbO2, Pb2O3, Pb3O4, Sb2O3, Sb2O4, Sb2O5, GeO, GeO2, Bi2O3, Bi2O4, and Bi2O5; conductive polymers such as polyacetylene; Li-Co-Ni-based materials, etc. may be used.
[0029] The material that can be used for the cathode current collector is not particularly limited. The cathode current collector preferably does not cause a chemical change when used in a battery and has a relatively high conductivity. For example, copper, stainless steel, aluminum, nickel, titanium, fired carbon, those with a surface treatment of carbon, nickel, titanium, silver, etc. on the surface of copper or stainless steel, aluminum-cadmium alloy, etc. can be used. Also, similar to the anode current collector, fine irregularities can be formed on the surface to strengthen the binding force of the cathode active material. It may be used in various forms such as films, sheets, foils, nets, porous bodies, foams, non-woven bodies, etc. Furthermore, the cathode current collector may generally have a thickness of 3 μm to 500 μm.
[0030] In one embodiment of the present invention, the separation membrane may be an organic / inorganic composite porous SRS (Safety-Reinforcing Separators) separation membrane. The SRS separation membrane may have a structure in which a coating layer component containing inorganic particles and a binder polymer is applied on a polyolefin-based separation membrane substrate.
[0031] Such an SRS separation membrane does not generate high-temperature heat shrinkage due to the heat resistance of the inorganic particles. Therefore, even if the electrode assembly penetrates through by a needle-shaped conductor, the elongation rate of the safety separation membrane can be maintained.
[0032] The SRS separator may have a uniform pore structure formed by the interstitial volume between inorganic particles, which are a component of the coating layer, as well as the pore structure contained in the separator substrate itself. The pores can not only significantly reduce external impacts on the electrode assembly, but also allow smooth movement of lithium ions through the pores, and a large amount of electrolyte can be filled to show a high impregnation rate, thereby improving the performance of the battery.
[0033] In one embodiment of the present invention, the separator may be sized according to the width dimension (perpendicular to the longitudinal dimension in which the separator is expanded) of the separator so that the separator extends outward from both sides beyond the edges corresponding to the adjacent anode and cathode (hereinafter, "excess portion"). In addition, the separator may be configured to have a structure in which a coating layer thicker than the thickness of the separator is formed on one or both sides of the excess portion of the separator to prevent the separator from shrinking. For details regarding the thick coating layer of the excess portion extending outward from the separator, refer to Korean Patent Publication No. 10-2016-0054219, the entire contents of which are incorporated herein by reference. In one embodiment of the present invention, the excess portion of the separator may be 5% to 12% in size based on the width of the separator. In another embodiment of the present invention, the coating layer may be coated on both sides of the separator with a size of 50% to 90% in size based on the width of the excess portion of the separator on one side. In addition, the widths of the coating layers on both sides may be the same or different.
[0034] In one embodiment of the present invention, the coating layer may contain inorganic particles and a binder polymer.
[0035] In one embodiment of the present invention, examples of the polyolefin-based separation membrane component include high density polyethylene, linear low density polyethylene, low density polyethylene, ultra-high molecular weight polyethylene, polypropylene, or derivatives thereof.
[0036] In one embodiment of the present invention, the thickness of the coating layer may be smaller than the thickness of the first electrode or the second electrode. In a specific example, the thickness of the coating layer may be 30% to 99% of the thickness of the first electrode or the second electrode.
[0037] In one embodiment of the present invention, the coating layer may be formed by wet coating or dry coating.
[0038] In one embodiment of the present invention, the substrate and the coating layer are present in a form of anchoring in which the pores on the surface of the polyolefin-based separator substrate and the coating layer are intertwined, and the separator substrate and the active layer can be physically strongly bonded. The thickness ratio of the substrate and the active layer of the separator may be 9:1 to 1:9. Preferably, the thickness ratio may be 5:5.
[0039] In one embodiment of the present invention, the inorganic particles may be inorganic particles commonly used in the art. The inorganic particles interact with each other to form micropores in the form of empty spaces between the inorganic particles, and at the same time, can help structurally maintain the physical form of the coating layer. In addition, the inorganic particles generally have physical properties that do not change even at high temperatures of 200°C or higher, so that the organic / inorganic composite porous film formed has excellent heat resistance.
[0040] In addition, the material that can be used for the inorganic particles is not particularly limited, but is preferably an electrochemically stable material. That is, the inorganic particles that can be used in the present invention are not particularly limited as long as they do not undergo oxidation and / or reduction reactions in the operating voltage range of the applied battery (for example, 0 to 5 V based on Li / Li+). In particular, when inorganic particles with ion transfer ability are used, the ion conductivity in the electrochemical element can be increased to improve performance. Therefore, it is preferable to use inorganic particles with as high an ion conductivity as possible. In addition, when the inorganic particles have a high density, it is difficult to disperse the inorganic particles during coating, which increases the weight of the battery during battery manufacture. Therefore, it is preferable to use inorganic particles with as low a density as possible. In addition, in the case of an inorganic material with a high dielectric constant, it contributes to an increase in the degree of dissociation of the electrolyte salt, for example, lithium salt, in the liquid electrolyte, and can improve the ion conductivity of the electrolyte.
[0041] For the above reasons, the inorganic particles may be at least one type selected from the group consisting of inorganic particles having piezoelectricity and inorganic particles having lithium ion transport ability.
[0042] The piezoelectric inorganic particles are non-conductors at normal pressure, but when a certain pressure is applied, they are materials that have the property of conducting electricity due to changes in their internal structure. They are also materials that exhibit high dielectric constant characteristics with a dielectric constant of 100 or more. The piezoelectric inorganic particles are also materials (e.g., separators) that have the function of generating electric charges when stretched or compressed by applying a certain pressure, with one side being positively charged and the other side being negatively charged, thereby generating a potential difference between both sides.
[0043] When inorganic particles having the above characteristics are used as a coating layer component, if an internal short circuit occurs between the electrodes due to an external impact such as a needle-shaped conductor, the inorganic particles coated on the separator may prevent the anode and cathode from coming into direct contact with each other. In addition, the piezoelectricity of the inorganic particles generates a potential difference within the particles, which causes electron transfer (i.e., a minute current flow) between the electrodes, resulting in a gradual decrease in the battery voltage and thus improved safety.
[0044] Examples of the inorganic particles having piezoelectricity include BaTiO3, Pb(Zr,Ti)O3 (PZT), Pb 1-x La x Zr 1-y Ti y O3(PLZT), PB(Mg3Nb 2 / 3 )O3-PbTiO3 (PMN-PT) and hafnia (HfO2), but is not limited thereto.
[0045] The inorganic particles having lithium ion transport ability refer to inorganic particles that contain lithium elements but do not store lithium but instead transport lithium ions. The inorganic particles having lithium ion transport ability can transport lithium ions through a type of defect present inside the particle structure. As a result, the lithium ion conductivity in the battery is improved, and thus the battery performance can be improved.
[0046] Examples of inorganic particles having the lithium ion transfer ability include lithium phosphate (Li3PO4), lithium titanium phosphate (Li x Ti y (PO4)3, 0 <x<2、0<y<3)、リチウムアルミニウムチタニウムホスフェート(Li x Al y Ti z (PO4)3, 0 <x<2、0<y<1、0<z<3)、(LiAlTiP) x O yis glass (0 < x < 4, 0 < y < 13), lithium lanthanum titanate (Li x La y TiO3, 0 < x < 2, 0 < y < 3), lithium germanium thiophosphate (Li x Ge y P z S w , 0 < x < 4, 0 < y < 1, 0 < z < 1, 0 < w < 5), lithium nitride (LixNy, 0 < x < 4, 0 < y < 2), SiS2 (Li x Si y S z , 0 < x < 3, 0 < y < 2, 0 < z < 4) - based glass and P2S5 (Li x P y S z , 0 < x < 3, 0 < y < 3, 0 < z < 7) - based glass, and may be one or more selected from the group consisting of, but not limited to, these.
[0047] The composition ratio of the inorganic particles and the binder polymer constituting the coating layer of the separation membrane is not particularly limited, but can be adjusted within the range of 10:90 to 99:1% by weight, and the range of 80:20 to 99:1% by weight is preferable. When the composition ratio is less than 10:90% by weight, the content of the polymer becomes excessively large, and the pore size and porosity due to the decrease in the empty space formed between the inorganic particles decrease, which may cause a decrease in the performance of the final battery. On the other hand, when it exceeds 99:1% by weight, since the polymer content is too small, the adhesive force between the inorganics weakens, and the mechanical properties of the final organic / inorganic composite porous separation membrane may decrease.
[0048] In one embodiment of the present invention, as the binder polymer, a binder polymer generally used in the art may be used.
[0049] The coating layer of the above organic / inorganic composite porous separation membrane may further contain other commonly known additives in addition to the aforementioned inorganic particles and binder polymer.
[0050] In one embodiment of the present invention, the coating layer can also be said to be an active layer.
[0051] As described above, after the electrode assembly 10 is assembled, a press applies heat and pressure to the laminate to bond the components together before the electrode assembly 10 is further manufactured (e.g., moved to a battery case). Such application of heat and pressure may be performed in several stages, including an initial primary heat pressing stage followed by a secondary heat pressing operation. To perform such heat pressing stages, a press may be provided, such as that shown in FIG. 6(a) and FIG. 6(b).
[0052] 6(a), the first press unit 50 can apply pressure to the laminate S in a heated and fixed state. The first press unit 50 includes a pair of first pressurizing blocks 50a, 50b, and may further include a gripper 51 capable of fixing the laminate S. In fixing the laminate S, the gripper 51 can fix the laminate S by pressing the upper and lower surfaces of the laminate S against each other along the stacking direction Y in order to fix the relative positions of the first electrode 1, the second electrode 2, and the separator 4.
[0053] The pair of first pressure blocks 50a, 50b of the first press section 50 may move toward or away from each other. The pair of first pressure blocks 50a, 50b may compress either or both of the laminate S and the gripper 51 as they move toward each other.
[0054] In one embodiment, the first press section 50 may apply heat and pressure to the laminate S to reduce or eliminate the spaces between the first electrode 1, the separator 4, and the second electrode 12 contained in the laminate S to bond such components of the laminate S.
[0055] As shown, the pressure surface of each of the pair of first pressure blocks 50a, 50b configured for contacting and applying pressure to the laminate S may be provided in a plane. At least one of the pair of first pressure blocks 50a, 50b may include a gripper groove 52 having a shape corresponding to the fixing portion 51b of the gripper 51 described below. In the example shown in FIG. 6(a), each of the pair of first pressure blocks 50a, 50b includes four gripper grooves 52 corresponding to the four fixing portions 51b. However, the number of gripper grooves 52 may be more or less. Preferably, the number of gripper grooves 52 should match the number of fixing parts used.
[0056] The gripper 51 may include a main body 51a and a plurality of fixing portions 51b. The main body 51a may have a length along the x-axis and a height along the y-axis that are the same or approximately the same as the length and height of the laminate S along the respective axes, as in the illustrated arrangement. In one embodiment, the main body 51a may have a height that is longer than the length of the laminate S in the x-axis and greater than the height of the laminate S in the y-axis. The fixing portion 51b may preferably be a rod, column or plate extending along the width direction (z-axis) of the laminate S. Here, the length of the x-axis of the laminate S means the part where the distance from one end of the laminate S to the other end is the longest, and the height of the y-axis may mean the distance in the direction of the laminate S. The width of the laminate S in the stacking direction, the z-axis, may mean the distance in the direction perpendicular to both the x-axis and the y-axis.
[0057] The fixing parts 51b may be provided in two rows, one row adjacent to the pressing surface of the pressing block 50a, and the other row adjacent to the pressing surface of the pressing block 50b. The position of each of the fixing parts 51b may be adjusted in the height direction of the main body 51a. In this manner, each of the fixing parts 51b can fix the relative positions of the first electrode 1 and the second electrode 12 in the stack S, and the position of the stack S, on the top and bottom surfaces of the stack S, and preferably along its width.
[0058] In one embodiment, during operation, the first press section 50 may use a pair of pressure blocks 50a, 50b to compress the laminate S for 5 to 20 seconds in an environment with an ambient temperature of 45°C to 75°C and a pressure of 1 MPa to 2.5 MPa.
[0059] In one embodiment, the second press section 60 may perform a second compression on the laminate S that has already been primarily compressed by heating and pressing the laminate S that has been preliminarily heated and compressed by the first press section 50 .
[0060] As shown in Fig. 6(b), the second press section 60 includes a pair of second pressurizing blocks 60a, 60b. The pair of pressurizing blocks 60a, 60b may be moved toward or away from each other. The pair of pressurizing blocks 60a, 60b can apply pressure to the top and bottom surfaces of the laminate S while moving toward each other to compress the laminate.
[0061] As shown, the pressure surface of each of the pair of second pressure blocks 60a, 60b configured for contacting and compressing the laminate S may be provided in a plane. As shown in the example, in one embodiment, grooves such as the groove for the fixing portion 51b may be omitted from the second pressure blocks 60a, 60b. In other embodiments, at least one of the pair of second pressure blocks 60a, 60b may include one or more grooves shaped to correspond to the fixing portion 51b of the gripper 51.
[0062] In one embodiment, during operation, the second press section 60 may compress the laminate primarily compressed by the first press section 50 for 5 to 60 seconds under temperature conditions of 50°C to 90°C and pressure conditions of 1 MPa to 6 MPa. In one embodiment, the second press section 60 may heat and press only a portion of the laminate S where (or before) the gripper 51 is located that is not heated and pressed by the first press section 50. In another embodiment, the second press section 50 may heat and press the entire upper and lower surfaces of the laminate.
[0063] In one embodiment, the first press unit 50 initially compresses the heated laminate S to bond together components included in the laminate S where the grippers 51 are not located, and fixes the upper and lower surfaces of the laminate S with the grippers 51, thereby reducing or eliminating the space between the first electrode 1, the separator 4 and the second electrode 12 during bonding.
[0064] In one embodiment, the second press unit 60 can pressurize and heat the laminate S that has been previously bonded by the first press unit 50 and from which the gripper 51 has been removed. Thus, the second press unit 60 can reduce or eliminate the space between the first electrode 1, the separator 4, and the second electrode 12 included in the laminate S in order to bond such components of the laminate S together in the area of the laminate S where the gripper 51 previously pressed the laminate S during the initial pressing operation by the first press unit 50. In one embodiment, each of the pair of second pressing blocks 60a, 60b may be a rectangular block in the shape of a rectangular parallelepiped. In one embodiment, the pair of second pressing blocks 60a, 60b may have the flat pressing surface described above.
[0065] In one embodiment, each of the pair of first press blocks 50a, 50b of the first press section 50 may have a flat press surface. In one embodiment, each of the pair of second press blocks 60a, 60b of the second press section 60 may have a groove having a shape corresponding to the fixing portion 51b of the gripper 51.
[0066] In one embodiment, the fixing portion 51b may include a thermally conductive material such as a thermally conductive metal material selected from the group consisting of aluminum and iron. By conducting heat to the laminate S, when the first press portion 50 compresses the laminate S fixed by the gripper 51, the space between the electrodes 11, 12 and the separator 4 may be reduced or eliminated, and the electrodes 11, 12 and the separator 4 may be bonded to each other.
[0067] In one embodiment, the second press section 60 may not compress areas of the laminate S where the grippers 51 were previously located, but instead may only compress areas of the laminate S where the grippers were not previously located and areas not pressed by the first press section 50.
[0068] In addition, the pair of first pressurizing blocks 50a, 50b may each be a rectangular block having a rectangular parallelepiped shape. In one embodiment, the pair of first pressurizing blocks 50a, 50b may have the flat pressurizing surfaces described above.
[0069] Either one or both of the first and second press units 50, 60 may include a press heater (not shown) and may be configured to heat a portion of the laminate S of the first and second electrodes 1 and the separator 4 when each pair of first and second press blocks 50a, 50b, 60a, 60b presses the laminate. In this manner, when the laminate S is pressed by the first and second press units 50, 60, the thermal fusion between the first electrode 1, the separator 4 and the second electrode 2 is more firmly performed, and stronger adhesion can be formed between these layers.
[0070] When the laminate S is pressed by the heated press unit, the inside of the external separation membrane 5 surrounding the outermost periphery of the laminate S can be bonded to the side end portions 6 of the first and second electrodes 1 and 2 in the lateral direction Z exposed to the adjacent external separation membrane 5 through openings characterized by the absence of the folding portion P as well as adjacent portions (e.g., folding portions P) of the winding separation membrane 4.
[0071] Therefore, by bonding the components of the electrode assembly 10 in this manner, loosening of the folding of the laminate S can be prevented, improving the stability of the battery. In addition, a separate adhesive tape or tool for preventing loosening of the laminate S is not required, shortening the manufacturing time and improving the process efficiency.
[0072] At least one exterior surface of a laminate S according to the present invention may include two or more patterns having different characteristics or heights than other areas on that surface.
[0073] In one embodiment, referring to Figures 4 and 5, the surface of the laminate S may include a first region P1 and a second region P2 having different characteristics or heights on the surface. For example, the first region P1 may be an area bounded by a gripper (e.g., gripper 51, specifically the fixed portion 51b of the gripper), and the second region P2 may be an area not bounded by the gripper. Thus, the width of the first region P1 may correspond to the width of the gripper, specifically the width of the fixed portion 51b of the gripper.
[0074] The first region P1 and the second region P2 may appear when the stack S is pushed by the gripper in the process operation described above.
[0075] The separator 4 included in the laminate S of the electrode assembly may have little binder component and low adhesive strength. Therefore, when the laminate S is pressurized, the first electrode 1 and the second electrode 2 may be deformed by the pressure applied to the laminate S.
[0076] Therefore, the electrode assembly 10 according to the present invention may be manufactured by fixing the upper and lower surfaces of the laminate S with grippers and applying a primary pressure to fix the first electrode 1 and the second electrode 2, and then removing the grippers and applying a secondary pressure.
[0077] As a result, the first region P1 and the second region P2 may differ in at least one of the properties and height. In one example, the property may be the shade or hue of at least one surface of the laminate. In another example, the property may be the air permeability of the separator 4 or the adhesion between the electrodes and the separator. The adhesion may refer to the amount of force required to peel the separator 4 from the electrodes 1, 2.
[0078] Two or more first regions P1 and two or more second regions P2 may be included. Furthermore, the first regions P1 may be spaced apart from one another, and the second regions P2 may also be spaced apart from one another.
[0079] In one embodiment, the number of first regions P1 may be less than the number of second regions P2. For example, when the number of first regions P1 in the electrode assembly 10 is N (N is a positive integer other than 0), the number of second regions P2 may be N+1.
[0080] The first region P1 and the second region P2 may be alternately positioned along the width direction X of the electrode assembly 10 or the laminate S. In addition, at least one boundary of the first region P1 may be in contact with at least one boundary of the second region P2.
[0081] In the electrode assembly 10 according to the present invention, the portions of the upper and / or lower surface of the laminate S where the grippers 51 (specifically, the fixed portions 51b of the grippers) engage may have a darker shade than the portions where the grippers 51 do not engage while being heat pressed by the first press unit 50. In this embodiment, the portions where the fixed portions 51b of the grippers 51 engage are the first region P1, and the portions where the fixed portions 51b of the grippers 51 do not engage are the second region P2.
[0082] Furthermore, the electrode assembly 10 according to the present invention may include a step between the first region P1 and the second region P2. That is, the height of the upper and / or lower surface portion of the laminate S engaged with the gripper 51 (particularly the fixed portion 51b of the gripper) may be different from the height of the upper and / or lower surface portion of the laminate S not engaged with the fixed portion 51b of the gripper 51. When the portion engaged with the gripper is the first region P1 and the portion not engaged with the gripper is the second region P2, the surface of the electrode assembly 10 may include a surface step, and the first region P1 may be higher than the second region.
[0083] The width of the first region P1 may be smaller than the width of the second region P2 in the electrode assembly 10. In other words, when the total area of one side of the laminate S including the first region P1 and the second region P2 is taken as 100%, the area of the first region P1 may be 30% to 50% of the area of the one side.
[0084] The electrode assembly 10 according to the present invention can minimize the width of the components of the gripper 51 that mesh with the electrode assembly 10, and can minimize the deviation in characteristics or height between the first region P1 and the second region P2. When the variation in characteristics or height between the first region P1 and the second region P2 is minimized, the overall characteristics or height of the electrode assembly 10 can become more uniform.
[0085] In addition, if the area of the first region P1 is less than 30% of the area of one side of the laminate S, there is a higher possibility that the electrodes of the electrode assembly 10 will move before being fixed by bonding, resulting in a lower energy density of the electrode assembly. On the other hand, if the area of the first region P1 exceeds 50% of the area of one side of the laminate S, a problem may occur in that the bonding of the components in the laminate S cannot ensure the desired minimum adhesive strength.
[0086] The surface on which the pattern is formed may be any of the upper surface, the lower surface, or both the upper and lower surfaces of the laminate S from both ends of the laminate S in the lamination direction.
[0087] In this specification, "adhesive strength" refers to the adhesive strength between the first electrode 1 and the separator, or between the second electrode 2 and the separator. The method for measuring the adhesive strength of the separator according to the present invention is not particularly limited. According to one measuring method, a sample having a width of 55 mm and a length of 20 mm is attached to each slide glass, and the electrode is positioned on the adhesive surface of the slide glass. Then, a 90° peel test is performed at a speed of 100 mm / min according to the test method specified in ASTM-D6862, and each sample is tested. That is, the edge of the separator is pulled upward at 90° to the slide glass at a speed of 100 mm / min so as to peel the separator from the electrode along the width direction of the sample (i.e., peel from 0 mm to 55 mm). Using such a test method, the adhesive strength between the electrode and the separation membrane in the first region P1 (hereinafter, the adhesive strength of the first region P1) may be 3 gf / 20 mm to 25 gf / 20 mm, and the adhesive strength between the electrode and the separation membrane in the second region P2 (hereinafter, the adhesive strength of the second region P2) may be 4 gf / 20 mm to 30 gf / 20 mm.
[0088] The difference in adhesive strength between separation membrane 4 and electrodes 1, 2 in first region P1 and second region P2 may be 0.1 gf / 20 mm to 11 gf / 20 mm.
[0089] According to one embodiment of the present invention, referring to FIG. 2, the intermediate adhesive strength of the first region P1 of the electrode assembly (i.e., the adhesive strength of one region) may be 3gf / 20mm to 10gf / 20mm, preferably 5gf / 20mm to 6gf / 20mm.
[0090] According to one embodiment of the present invention, the upper surface adhesive strength of the first region P1 of the electrode assembly (ie, the adhesive strength of one region in FIG. 2) may be 8 gf / 20 mm to 20 gf / 20 mm, preferably 9 gf / 20 mm to 14 gf / 20 mm.
[0091] According to one embodiment of the present invention, the bottom adhesive strength of the first region P1 of the electrode assembly (ie, the adhesive strength in the three regions in FIG. 2) may be 9 gf / 20 mm to 25 gf / 20 mm, preferably 9 gf / 20 mm to 12 gf / 20 mm.
[0092] According to one embodiment of the present invention, the intermediate adhesive strength of the second region P2 of the electrode assembly may be 4 gf / 20 mm to 15 gf / 20 mm, preferably 5 gf / 20 mm to 11 gf / 20 mm.
[0093] According to one embodiment of the present invention, the upper surface adhesive strength of the second region P2 of the electrode assembly may be 5 gf / 20 mm to 25 gf / 20 mm, preferably 7 gf / 20 mm to 21 gf / 20 mm.
[0094] According to one embodiment of the present invention, the lower surface adhesive strength of the second region P2 of the electrode assembly may be 7 gf / 20 mm to 30 gf / 20 mm, preferably 10 gf / 20 mm to 22 gf / 20 mm.
[0095] According to one embodiment of the present invention, the adhesive strength between the anode and the separator and the adhesive strength between the cathode and the separator may be the same or different.
[0096] If the adhesive strength between the first region P1 and the second region P2 is less than 4 gf / 20 mm, the adhesive strength of the electrode assembly 10 will be low, and folding may loosen when the electrode assembly 10 or the laminate S is moved during the manufacturing process, which may result in a problem of the separation membrane 4 folding.
[0097] If the adhesive strength of the first region P1 exceeds 15 gf / 20 mm and the adhesive strength of the second region P2 exceeds 26 gf / 20 mm, the breathability and impregnation of the separator 4 will decrease, making it difficult for the electrolyte to penetrate into the electrode assembly 10, which may reduce the initial capacity of the electrode assembly 10 and increase the initial resistance value.
[0098] In the present invention, the “air permeability” of the electrode assembly refers to the air permeability of the separator 4 of the electrode assembly 10 .
[0099] In the present invention, the method for measuring the air permeability of the separation membrane is not particularly limited. In the methods used and further discussed in this specification, the air permeability was measured according to a method commonly used in the industry, i.e., the JIS Gurley measurement method, using a Toyoseiki Gurley type Densometer (No. 158). That is, the air permeability of the separator was obtained by measuring the time it takes for 100 ml (or 100 cc) of air to pass through a 1 square inch separation membrane at room temperature (i.e., 20°C to 25°C) at a pressure of 0.05 MPa.
[0100] In addition, unless otherwise specified, "air permeability" refers to the air permeability of all the separators in the electrode assembly, and the air permeability of each separator may be independently the same or different. Also, as described above, the top surface air permeability, bottom surface air permeability, and middle surface air permeability may be defined according to the position of the electrode assembly.
[0101] The difference in air permeability between the first region P1 and the second region P2 may be 2 seconds / 100 ml to 25 seconds / 100 ml.
[0102] According to one embodiment of the present invention, the intermediate air permeability of the first region P1 of the electrode assembly may be 70sec / 100ml to 90sec / 100ml, preferably 75sec / 100ml to 86sec / 100ml.
[0103] According to one embodiment of the present invention, the upper surface air permeability of the first region P1 of the electrode assembly may be 80 sec / 100 ml to 110 sec / 100 ml, preferably 80 sec / 100 ml to 98 sec / 100 ml.
[0104] According to one embodiment of the present invention, the underside air permeability of the first region P1 of the electrode assembly may be 80 sec / 100 ml to 110 sec / 110 ml, preferably 80 sec / 100 ml to 98 sec / 100 ml.
[0105] According to one embodiment of the present invention, the intermediate air permeability of the second region P2 of the electrode assembly may be 70sec / 100ml to 100sec / 100ml, preferably 75sec / 100ml to 84sec / 100ml.
[0106] According to one embodiment of the present invention, the upper surface air permeability of the second region P2 of the electrode assembly may be 80 sec / 100 ml to 110 sec / 100 ml, preferably 84 sec / 100 ml to 101 sec / 100 ml.
[0107] According to one embodiment of the present invention, the underside air permeability of the second region P2 of the electrode assembly may be 80 sec / 100 ml to 110 sec / 100 ml, preferably 84 sec / 100 ml to 101 sec / 100 ml.
[0108] According to one embodiment of the present invention, the bottom surface air permeability may be equal to or smaller than the top surface air permeability. Also, the intermediate air permeability may be equal to or smaller than the bottom surface air permeability. That is, the magnitudes of the top surface air permeability, the bottom surface air permeability, and the intermediate air permeability can satisfy the following formula 1.
[0109] [Formula 1] Top air permeability ≧ Bottom air permeability ≧ Intermediate air permeability
[0110] The result of Equation 1 above represents the result of the pressure generated in the process of heating and pressurizing the electrodes and the separator and when the electrodes and the separator are laminated.
[0111] According to one embodiment of the present invention, if the air permeability of the separator 4 in the first region P1 and the second region P2 is less than 70 sec / 100 ml, the impregnation of the electrolyte is low, the ion migration path is blocked, and the performance of the electrode assembly 10 may be deteriorated. If the air permeability of the separator 4 in the first region P1 and the second region P2 exceeds 110 sec / 100 ml, the adhesive strength between the separator and the first electrode 1 and the second electrode 2 is reduced, and the first and second electrodes 1, 2 of the electrode assembly 10 may protrude and be formed on the exterior of the battery.
[0112] While the present invention has been described above with reference to preferred embodiments, it will be understood that those skilled in the art can make various modifications and variations of the present invention without departing from the spirit and scope of the present invention as set forth in the following claims.
[0113] Working Example 1) Example 1 Nineteen anodes, 20 cathodes and a separation membrane were stacked on a stack S on a stack table.
[0114] More specifically, the anode and cathode were supplied in the form of being cut from an anode sheet and a cathode sheet, respectively, and the separator was supplied in the form of a separator sheet. Then, the stack table was rotated to fold the supplied separator, thereby stacking the anode, cathode, and separator. At this time, stacking was performed while pushing the upper surface of the stack S downward toward the stack table using a gripper in order to fix the position of the stack S relative to the stack table.
[0115] After preparing the laminate, the laminate was gripped with a gripper and heated under conditions of an ambient temperature of 70° C. and a pressure of 1.91 MPa, while pressing the laminate for 15 seconds using the first press unit 50 to carry out a first heat pressing step.
[0116] After the first heat pressing step, the grippers were released from the laminate, and the temperature of the second press part 60 was heated to 70°C (temperature condition), and a pressure of 2.71 MPa (pressure condition) was applied to the laminate by the pressure block of the press for 10 seconds (press time) to produce the electrode assembly of Example 1 through a second heat pressing step.
[0117] The above-mentioned disclosure of the present invention may be applied to the manufacturing process of the electrode assembly.
[0118] 2) Examples 2 to 12 Electrode assemblies of Examples 2 to 12 were manufactured in the same manner as in Example 1, except that the second heat pressing step was performed under the temperature conditions, pressure conditions, and pressing times shown in the following Table 1. That is, the first heat pressing conditions of Examples 1 to 12 were the same.
[0119] [Table 1]
[0120] 3) Comparative Examples 1 to 5 Electrode assemblies of Comparative Examples 1 to 5 were manufactured in the same manner as in Example 1, except that the first heat pressing step was performed under the temperature conditions, pressure conditions, and pressing times shown in Table 2 below, and the second heat pressing step was not performed.
[0121] [Table 2]
[0122] The electrode assemblies of Examples 1 to 12 and Comparative Examples 1 to 5 manufactured under the conditions of Tables 1 and 2 were all picked up by a vacuum suction mechanism and tested. It was observed that the electrodes and the separator were separated from each other within 60 seconds for all the electrode assemblies of Comparative Examples 2 to 5.
[0123] That is, the electrode assemblies of Comparative Examples 1 to 5 had poor adhesion between the electrodes and the separator, whereas the electrode assemblies of the present application (first and second pressing processes) had good adhesion. Therefore, there was an excellent effect in preventing the electrode assembly from loosening and falling off.
[0124] In the case of Comparative Examples 6 and 7, the phenomenon of the electrode and separator being separated was not observed before 60 seconds, but damage to the electrode assembly was confirmed. This is presumed to have occurred because the primary pressing was performed under a pressure condition of 2.54 MPa (high pressure).
[0125] 4) Experimental Example 1 - Adhesion strength evaluation and voltage resistance evaluation After disassembling (i.e., layer separation) the electrode assemblies of Examples 1 to 12 and Comparative Examples 6 and 7 (in cases where separation of the electrode and separator was not observed before 60 seconds in the previous tests), the separated layers were analyzed to measure the adhesive strength between the upper end, lower end and middle surface of the laminate S. Specifically, the adhesive strength between the separator located at the bottom end of the laminate and the cathode was measured. In addition, the adhesive strength between the cathode located at the top end of the laminate and the separator was measured. Finally, the adhesive strength between the cathode located at the midpoint along the stacking direction of the laminate and the separator was measured.
[0126] The width and length of the cathode and separator sampled from each of the separated electrode assemblies were 55 mm and 20 mm, respectively. The sampled samples were attached to a glass slide such that the electrodes were located on the adhesive surface of the glass slide. The glass slide with the specimen attached was then mounted on an adhesion tester and tested at a 90° peel test at a speed of 100 mm / min according to the test method specified in ASTM-D6862 as discussed above. After ignoring any initial violent fluctuations, the force (g / mm) applied per sample width while the separator was peeled off from the electrode was measured.
[0127] The results are shown in Table 3 below.
[0128] [Table 3]
[0129] Furthermore, the withstand voltages of the electrode assemblies of Examples 1, 6 and 12 and Comparative Examples 1 to 7 were also measured.
[0130] The results are shown in Table 4 below. [Table 4]
[0131] From the results in Table 4, it was confirmed that the adhesive strength of Examples 1, 6 and 12 was superior to that of Comparative Example 1 in which only the first heat pressing step was performed under similar conditions to the Examples.
[0132] Furthermore, the results in Table 4 confirm that the withstand voltages of Examples 1, 6 and 12, in which the first heat press step was carried out under higher temperature and pressure conditions than the comparative example, were in the range of 1.56 kV or more and 1.8 kV or less.
[0133] That is, the electrode assembly of the present invention has excellent adhesive strength and also has characteristics in terms of withstand voltage suitable for use as an electrode assembly, and a withstand voltage of 1.8 kV or less was confirmed.
[0134] This is believed to be because the electrode assembly was manufactured using a manufacturing method that included both the first and second heat press steps.
[0135] 5) Experimental Example 2 - Air permeability evaluation Among Examples 1 to 12, Examples 1, 6 and 12 and Comparative Example 1, which were different only in the temperature condition of the second press, were evaluated for air permeability.
[0136] Specifically, the separation membrane was collected from the electrode assemblies of Examples 1, 6, and 12, and then cut into a separation membrane sample having a size of 5 cm x 5 cm (width x length), and then the separation membrane sample was washed with acetone.
[0137] Thereafter, in accordance with the JIS Gurley measurement method, the air permeability of Examples 1, 6 and 12 was measured by measuring the time it took for 100 ml (or 100 cc) of air to pass through 1 square inch of the separation membrane under room temperature and a pressure of 0.05 MPa using a Toyoseiki Gurley type Densometer (No. 158).
[0138] The results are shown in Table 5. [Table 5]
[0139] From the results of Table 5, it was confirmed that when the second heat pressing conditions according to the present invention are met, the air permeability corresponding to each position is less than 120 sec / 100 ml, which is a level suitable for use as an electrode assembly. In addition, it was confirmed that the deviation in air permeability at each position is less than 20 sec / 100 ml, which is a level that can be determined to be uniform. In other words, it was confirmed again that the electrode assembly manufactured by the manufacturing method according to the present invention has uniform performance.
[0140] It was also confirmed that the deviation in air permeability between each position was less than 20 sec / 100 ml, which was a level that could be determined to be uniform.
[0141] Among them, it was confirmed that the deviation in air permeability was the smallest in Example 1 where the temperature condition was 70°C.
[0142] Through the above experimental examples, it was confirmed that the electrode assembly according to the present invention has appropriate and uniform air permeability and adhesive strength.
[0143] On the other hand, in the case of Comparative Example 1, the variation in air permeability at each position was smaller than in the Example, but the upper surface air permeability and the lower surface air permeability were each independently less than 80 sec / 100 ml, and it was confirmed that the safety was lower than that of the electrode assembly according to the present invention. This is believed to be because, unlike the manufacturing process of the electrode assembly according to the present invention, only the first heat press was carried out.
Claims
1. a plurality of electrodes arranged in the laminate along a lamination axis; each electrode in the stack is separated from one of the electrodes in the stack by a respective separator membrane located therebetween along the stack axis; At least one exterior surface of the laminate includes a pattern comprised of first and second regions; A second portion of the stack corresponding to the second region has a different characteristic or height than a first portion of the stack corresponding to the first region.
2. a second portion of the stack corresponding to the second region has different properties than a first portion of the stack corresponding to the first region; 2. The electrode assembly of claim 1, wherein the characteristics include any one of the shade, hue, of at least one outer surface of the laminate, the air permeability of the separator portions in the first and second regions, and the adhesive strength between the electrodes and the separator portions in the first and second regions.
3. 2. The electrode assembly of claim 1, wherein at least one outer surface of the laminate including the pattern is a top surface, a bottom surface, or both a top surface and a bottom surface of the laminate from opposing sides of the laminate along the stacking axis.
4. the pattern includes two or more of the first regions and two or more of the second regions; The electrode assembly of claim 1 , wherein the first regions are spaced apart from one another and the second regions are spaced apart from one another.
5. The first regions and the second regions are alternately positioned along the width direction of the laminate, The electrode assembly of claim 1 , wherein the width direction is transverse to the stacking axis.
6. The electrode assembly of claim 1 , wherein the first region has a width that is less than a width of the second region.
7. The electrode assembly of claim 1 , wherein the pattern includes a plurality of the second regions, and the number of the first regions is less than the number of the second regions.
8. the separators are bonded to the electrodes, and a peel force is applied to an edge of one of the separators to peel one of the separators from each of the electrodes bonded to the separator at a speed of 100 mm / min along the lamination axis; a peel force at a first portion corresponding to the first region is different from a peel force at a second portion corresponding to the second region; The electrode assembly of claim 1 , wherein a difference in peel force between the first portion and the second portion is 0.1 gf / 20 mm to 11 gf / 20 mm.
9. The separation membrane has an air permeability of 100 ml / sec per square inch of each separation membrane at a pressure of 0.05 MPa; 2. The electrode assembly of claim 1, wherein a permeability value of the separator in a first portion corresponding to the first region is different from a permeability value of the separator in a second portion corresponding to the second region, and a difference in permeability between the first portion and the second portion is 2 sec / 100 ml to 25 sec / 100 ml.
10. the separators are provided with elongated separator sheets folded between each of the separators so as to extend from the stack axis between each successive electrode along a serpentine path traversing back and forth along a transverse direction perpendicular to the stack axis; 2. The electrode assembly of claim 1, wherein each electrode in the stack includes a first side edge and a second side edge on laterally opposing sides of each electrode.
11. The electrode assembly of claim 10 , wherein the laminate further comprises an outer separator membrane surrounding the laminate.
12. The electrode assembly of claim 11 , wherein the external separator is integral with the separator.
13. 12. The electrode assembly of claim 11, wherein an inner side of the outer separator is thermally bonded to at least one of a folded portion of the extended separator or a first side end or a second side end of at least one electrode of the stack.
14. The electrode assembly of claim 1 , wherein each of the electrodes in the stack is thermally bonded to an adjacent one of the separators.
Citation Information
Patent Citations
JP1970005056Y1
Press device of wound element
JP2009259719A
Laminated electrode body and method of manufacturing laminated electrode body
JP2015141791A
Electrode assembly and method for manufacturing the same
JP2018532240A
Electrode assembly manufacturing apparatus and manufacturing method
JP2023552532A